Gradual pairwise comparison and stochastic choice - Rohan Dutta (Theoretical Economics, 2020)
Guided by evidence from eye-tracking studies of choice, pairwise comparison is assumed to be the building block of the decision-making procedure. A decision-maker with a rational preference may nevertheless consider the constituent pairwise comparisons gradually, easier comparisons preceding difficult ones. Facing a choice problem she may be unable to complete all relevant comparisons and choose with equal odds from alternatives not found inferior. Stochastic choice data consistent with such behaviour is characterized and used to infer the underlying preference relation and the order of pairwise comparisons. The choice procedure offers a novel rationale for behavioural phenomena such as the similarity effect and violations of stochastic transitivity and regularity.
Keywords: D01; D91; 330; Revealed preference; bounded rationality; stochastic choice